MODELLING OF RADIONUCLIDE MIGRATION IN THE SYSTEM OF NUCLEAR POWER PLANT BIOLOGICAL PONDS - Кутлахмедов, Ю.; Бевза, А. (Proceedings of National Aviation University (archive), 2012)
Migration of radionuclide coming from nuclear power plant into the system of biological ponds and then into the water reservoir-cooler is considered in the article. The theme of the work is modeling of radionuclide migration process in the system of biological ponds on the example of the Pivdennoukrainska nuclear power plant using chamber models method. Typical water ecosystem consisting of three chambers (chamber-water, chamber-biota and chamber-bed silt) was the basis taken by the authors. Application of chamber models method allowed authors to develop the dynamic chamber model of radionuclide migration in nuclear power plant biological ponds. This model allows to forecast values and dynamics of radioactive water pollution based on limited ecosystem monitoring data. Thus, parameters of radioactive capacity of nuclear power plant biological ponds system and water reservoir-cooler were modeled by authors, the estimation and prognosis of radionuclide distribution and accumulation in the system of nuclear power plant biological ponds were done. Authors also explain the roles of basin water, biomass and bed silt in radionuclide deposition